2000
DOI: 10.7164/antibiotics.53.516
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide Esterase-producing Escherichia coli Clinically Isolated in Japan.

Abstract: Current Japanese clinical practice involves the usage of large amounts of new macrolides such as clarithromycin and roxithromycin for the treatment of diffuse panbronchiolitis, Helicobacter pylori and Mycobacterium avium complex infections. In this study, the phenotypes, genotypes, and macrolide resistance mechanisms of macrolide-inactivating Escherichia coll recovered in Japan from 1996 to 1997, were investigated.The isolation rate of erythromycin A highly-resistant E. coli (MIC > 1600 /xg/ml) in Japan slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…Unfortunately, there is little previously published data from other countries available for comparison of data, because most studies have focused on macrolide resistance in pathogenic bacteria from clinical settings and/or diseased hosts (1,3,4,6,7,9,11,12,(14)(15)(16)(17)(18)22). However, we can compare these results with those of an earlier study by Luna et al (8) on 615 randomly selected, commensal, gram-positive isolates from the same group of Lisbon children as the current study over the same time period.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is little previously published data from other countries available for comparison of data, because most studies have focused on macrolide resistance in pathogenic bacteria from clinical settings and/or diseased hosts (1,3,4,6,7,9,11,12,(14)(15)(16)(17)(18)22). However, we can compare these results with those of an earlier study by Luna et al (8) on 615 randomly selected, commensal, gram-positive isolates from the same group of Lisbon children as the current study over the same time period.…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom, azithromycin has been used for cystic fibrosis patients infected with P. aeruginosa (3). Recently, highly macrolide-resistant strains, producing erythromycin esterase (1,6) or macrolide 2Ј-phosphotransferase [MPH(2Ј)] (5, 7, 9), have been recovered with increasing frequency in clinical isolates of members of the family Enterobacteriaceae and also staphylococci (8). No reports, however, have yet been published regarding the presence of a macrolide-inactivating enzyme in P. aeruginosa.…”
Section: Detection and Characterization Of A Macrolide 2-phosphotransmentioning
confidence: 99%
“…Transfer of the macrolide resistance phenotype from these P. aeruginosa isolates could not be demonstrated, as the transfer frequencies to the recipient strain P. aeruginosa PAO2142Rp were less than 10 Ϫ8 . Enzymatic inactivation of macrolides using crude extracts with or without a cofactor (40 mM ATP, 40 mM GTP, 2 mM acetyl coenzyme A, 40 mM NAD, 40 mM NADP, 40 mM UDPG, or 80 mM GSH) was determined by measuring residual macrolide activity (6). It was demonstrated that the inactivation of oleandomycin using crude extracts from the two isolates was dependent on only ATP or GTP (Table 1).…”
Section: Detection and Characterization Of A Macrolide 2-phosphotransmentioning
confidence: 99%
“…Rachek et al [10] described the expression of the E. coli ereB gene in a parasitic Rickettsia prowazekii. The isolation rate of macrolide-inactivating E. coli (MIC v 1600 Wg ml 31 ) tends to increase in Japanese clinical samples [11].…”
Section: Introductionmentioning
confidence: 99%